Utilization Level of Assessment Strategies among Arts Education Teachers of Elementary Stage - Al Atoum, Monther Sameh Mohmmad; Alsaggar, Mowafaq Ali Sharif; Tubaishat, Taiesir Hamdi Ahmad (Dirasat: Educational Sciences, 2022)
Objectives: This study aims to identify the utilization level of assessment strategies among arts education teachers at the elementary stage. Methods: To achieve the aims of the study, a descriptive design based on a questionnaire was used. The study sample consisted of arts education teachers at the Jerash Directorate of Education during the first semester of the academic year 2018-2019. Results: The results of the study reveal that the utilization level of assessment strategies among arts education teachers of the elementary stage, as a whole, was moderate. Furthermore, the results show no statistical significance at (α = 0.05) between the mean scores of study sample estimations related to the utilization level of assessment strategies among arts education teachers of the elementary stage as a whole due to gender. They also reveal statistically significant differences due to educational qualification, in favor of teachers of higher education qualifications, and due to years of experience, in favor of teachers with ten or more years of experience. Conclusions: Training teachers of arts education on the utilization of assessment strategies and proposing pre-service courses addressing the employment of assessment and their strategies and their applications in the field of arts education.